Perancangan Sistem Informasi Pengolahan Data Penjualan Secara Kredit dan Controlling Stock Dengan Menerapkan Metode Backorder Pada Toko Master Menggunakan Bahasa Pemrograman Java dan Database MySql - J. Prayoga (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2019)
Had done the research on the Master Store, where the problems are used as the basis in writing this is a system of data processing sales on credit and controlling stock. Through the process of direct observation of the field has gained the weaknesses of the existing system. Although not entirely but more directed to a specific problem, it is expected to contribute significantly to the users of the system. The author designed the information system of data processing sales on credit and controlling stock based on Java Master Store, because with this information system will be faster, precise, and accurate. In designing this new system used the Java programming language and MySQL database, with the design of this new system the authors embody the system of data processing sales on credit and efficient controlling stock on the Master Store. Keywords: Credit Sales Data Processing And Controlling Stock, JAVA, MySQL